Kurikulum Bahasa Arab di Madrasah Aliyah: Studi Komparasi Kurikulum Bahasa Arab antara MA Darussholah dan MAN Jember 1: Arabic Language Curriculum in Madrasah Aliyah: A Comparative Study of Arabic Curriculum between MA Darussholah and MAN Jember 1 - Nuruddin Nuruddin (Fenomena, 2012)
Madrasah Aliyah, as a formal educational institution, plays a significant role in developing religious material, especially Arabic language material. However, Madrasah Aliyah is considered to have failed in achieving the goals of Arabic language teaching and learning. This is evidenced by the inability of STAIN Jember students to learn Arabic effectively. This research examines the differences in the managerial system of the Arabic curriculum between two institutions, namely MA Darussholah and MAN Jember 1. The results show that the Arabic curriculum at MA Darussholah is implemented in the aspects of planning, implementation, evaluation, and general development, with a focus on improving students' ability to read the Holy Book. Meanwhile, MAN Jember 1 also focuses on reading improvement, but its implementation is not supported by adequate meeting hours. Madrasah Aliyah sebagai lembaga pendidikan formal memiliki peran besar dalam pengembangan materi keagamaan, khususnya materi Bahasa Arab. Namun, Madrasah Aliyah dinilai gagal dalam mencapai tujuan pembelajaran Bahasa Arab. Hal ini dibuktikan dengan ketidakmampuan mahasiswa STAIN Jember dalam mempelajari Bahasa Arab. Penelitian ini mengkaji perbedaan sistem manajemen kurikulum Bahasa Arab di dua lembaga, yaitu MA Darussholah dan MAN Jember 1. Hasil penelitian menunjukkan bahwa kurikulum Bahasa Arab di MA Darussholah dilaksanakan dalam aspek perencanaan, implementasi, evaluasi, dan pengembangan umum yang berfokus pada peningkatan kemampuan siswa dalam membaca kitab suci. Sementara itu, MAN Jember 1 juga berfokus pada peningkatan kemampuan membaca, tetapi implementasinya tidak didukung oleh jumlah jam pertemuan yang memadai.